Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fgene.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Carcass and Meat Quality Traits in Montana Tropical® Composite Beef Cattle

Abstract: The Montana Tropical ® Composite is a recently developed beef cattle population that is rapidly expanding in Brazil and other tropical countries. This is mainly due to its improved meat quality and adaptation to tropical climate conditions compared to Zebu and Taurine cattle breeds, respectively. This study aimed to investigate the genetic architecture of ultrasound-based carcass and meat quality traits in Montana Tropical ® Composite beef cattle. Therefore, we estimated variance components and genetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 96 publications
(111 reference statements)
2
41
0
1
Order By: Relevance
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 89%
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 89%
“…Another relevant candidate region on BTA21 (at position: 14,830,000-16,650,000 bp) harboured four protein coding genes: SLCO3A1, SV2B, AKAP13 and KLHL25. The latter two genes were shown to be under positive selection in Creole cattle breeds 38 while SLCO3A1 is associated with marbling score in the Montana Tropical Composite beef cattle 39 and mediates inflammatory processes in intestinal epithelial cells through NF-kappa-B transcription activation in humans 40 . SV2B gene is among major genes enriched for the extracellular matrix (ECM) around the hair follicle in Changthangi goats 41 .…”
Section: Discussionmentioning
confidence: 99%
“…On BTA14, FAM110B and UBXN2B genes were identified to be associated with productive traits, reproductive traits (Grigoletto et al, 2019) and feed efficiency (Seabury et al, 2017). Flori et al (2009) has also reported FAM110 as selection signature for dairy cattle under artificial selection.…”
Section: Discussionmentioning
confidence: 99%